Monitoring the Effectiveness of Treatment in Women with Schizophrenia: New Specialized Cooperative Approaches - Mentxu Natividad; Mary V. Seeman; Jennipher Paola Paolini; Ariadna Balagué; Eloïsa Román; Noelia Bagué; Eduard Izquierdo; Mireia Salvador; Anna Vallet; Anabel Pérez; José A. Monreal; Alexandre González-Rodríguez (Brain Sciences, 2023)
Women with schizophrenia have specific health needs that differ from those of men and that change through successive life stages. We aimed to review the biopsychosocial literature on schizophrenia that addresses clinically important questions related to the treatment of women, including somatic morbi-mortality, hyperprolactinemia, comorbid substance use disorders, social risk factors, and medication effectiveness/safety. Data search terms were as follows: (Morbidity AND mortality) OR hyperprolactinemia OR (“substance use disorders” OR addictions) OR (“social risk factors”) OR (“drug safety” OR prescription) AND women AND schizophrenia. A secondary aim was to describe a method of monitoring and interdisciplinary staff strategies. Schizophrenia patients show an increased risk of premature death from cardiovascular/respiratory disease and cancer compared to the general population. The literature suggests that close liaisons with primary care and the introduction of physical exercise groups reduce comorbidity. Various strategies for lowering prolactin levels diminish the negative long-term effects of hyperprolactinemia. Abstinence programs reduce the risk of victimization and trauma in women. Stigma associated with women who have serious psychiatric illness is often linked to reproductive functions. The safety and effectiveness of antipsychotic drug choice and dose differ between men and women and change over a woman’s life cycle. Monitoring needs to be multidisciplinary, knowledgeable, and regular.